The Predictive Value of Lactate Dehydrogenase for Viral Suppression in Newly Diagnosed People Living With HIV on Antiretroviral Therapy: A Retrospective Cohort Study - Jin Y; Wang Y; Xia T; Ma Q (Infection and Drug Resistance)
Yong Jin,1,* Yan Wang,1,* Ting Xia,1 Qichao Ma2 1Department of Internal Medicine, Ningbo Yinzhou No.2 hospital, Ningbo, Zhejiang, People’s Republic of China; 2Department of Dermatology and Venereology, Ningbo Yinzhou No.2 hospital, Ningbo, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qichao Ma, Department of Dermatology and Venereology, Ningbo Yinzhou No.2 hospital, No.998 Qianhe North Road, Ningbo, Zhejiang, 315101, People’s Republic of China, Email mqc777@126.comPurpose: Rapid initiation of antiretroviral therapy (ART) in people living with HIV (PLWH) is crucial for achieving viral suppression and improving clinical outcomes. Serum lactate dehydrogenase (LDH) levels serve as a readily accessible and rapid clinical biomarker, has significant predictive potential in various viral diseases. This study aims to evaluate the predictive value of LDH levels for viral suppression in the context of rapid ART initiation.Patients and Methods: LDH levels were measured in 393 newly diagnosed PLWH who received rapid initiation of ART and were subsequently followed up. The PLWH were stratified based on tertile LDH levels and study endpoints. Kaplan-Meier analysis was conducted to generate survival curves, and Cox regression analysis was utilized to confirm the independent prognostic factors for viral suppression.Results: The overall viral suppression rate was 94.1%. Compared to the low LDH tertile, the middle and high LDH tertiles exhibited longer times to first viral suppression (38 vs 84 vs 88 days, respectively, P < 0.001). Kaplan-Meier analysis revealed that PLWH in high LDH tertile showed the worst prognosis for viral suppression (Log rank test, P< 0.001). Multivariate Cox regression analysis identified LDH tertile as a significant predictor of viral suppression (HR = 0.714, 95% CI = 0.553– 0.922, P = 0.010 for middle vs low tertile; HR = 0.575, 95% CI = 0.443– 0.747, P < 0.001 for high vs low tertile).Conclusion: LDH levels function as a prognostic indicator for predicting the timing of viral suppression in PLWH on ART. A comprehensive evaluation of LDH levels is beneficial in establishing risk stratification in the context of rapid ART initiation. Keywords: predictive value, lactate dehydrogenase, viral suppression, HIV